Colonial Origins of the Threefold Reality of Mozambique: fiscal capacity and labour systems - Kleoniki Alexopoulou; Dacil Juif (African Economic History Network (AEHN), 2015)
The question whether institutions in Africa were shaped by the metropolitan identity of the colonizer or by local conditions is lively debated in the African economic history literature. In this paper we contribute to this debate by revealing regional differences in tax capacity in the Portuguese colony of Mozambique. Samir Amin (1972) divided the African continent into three different "macro-regions of colonial influence": Africa of the colonial trade or peasant economy, Africa of the concession-owning companies and Africa of the labour reserves. Interestingly, we argue that Mozambique encompassed all three different "macro-regions" in one sole colony. In regression analysis we find differences in "tax capacity" along this threefold categorization. We use a newly compiled dataset that includes government revenue (direct/indirect taxes) raised on a district level between 1930 and the 1973, derived from the statistical yearbooks and national accounts of Mozambique. Focussing on one country has the advantage over cross country comparisons that one can keep the metropolitan identity constant. We conclude that the tax system developed as a response to the local conditions. and the differences between the three regions were exacerbated during colonial times.
Keywords: N17; N27; N37; N47; N57; N97; 330; Africa; economic history; colonialism; Mozambique; fiscal capacity; labour